Timeframe of socket cortication after tooth extraction: A retrospective radiographic study. Issue 1 (15th October 2017) - Bertl, Kristina; Kukla, Edmund Benjamin; Albugami, Rajaa; Beck, Florian; Gahleitner, André; Stavropoulos, Andreas
Abstract: Objectives: To assess the timeframe between tooth extraction and radiographically detectable socket cortication in humans. Methods: Two hundred and fifty patients with a CT scan ≤36 months after tooth extraction were included. First, three orthoradial multiplanar reconstruction slices, representing the major part of the extraction socket, were scored regarding the degree of bone healing as (i) healed, that is, complete/continuous cortication of the socket entrance, or (ii) non‐healed. Thereafter, based on the results of all three slices, the stage of cortication of the extraction socket, as one unit, was classified as (i) non‐corticated, that is, all three slices judged as non‐healed, (ii) partially corticated, that is, 1 or 2 slices judged as non‐healed, or (iii) completely corticated, that is, all three slices judged as healed. The possible effect of several independent parameters, that is, age, gender, timeframe between tooth extraction and CT scan, tooth type, extent of radiographic bone loss of the extracted tooth, tooth‐gap type, smoking status, presence of any systemic disease, and medication intake, on cortication status was statistically evaluated. Results: Three to 6 months after tooth extraction, 27% of the sockets were judged as non‐corticated and 53% were judged as partially corticated. After 9–12 months, >80% of the sockets were corticated, while some incompletely corticated sockets were detected up to 15 months after extraction. Each additional month after tooth extraction contributed significantly to a higher likelihood of a more advanced stage of cortication, while radiographic bone loss ≥75% significantly prolonged cortication time; no other independent variable had a significant effect. Conclusions: The results indicate a considerably long timeframe until complete cortication of an extraction socket, that is, 3–6 months after tooth extraction 3 of 4 sockets were still not completely corticated, and only after 9–12 months, complete cortication was observed in about 80% of the sockets.